Quasi-periodic injections of relativistic electrons in Saturn’s outer magnetosphere - Roussos,E; Krupp,N; Mitchell,DG; Paranicas,C; Krimigis,SM; Andriopoulou,M; Palmaerts,B; Kurth,WS; Badman,SV; Masters,A; Dougherty,MK (Icarus, 2016)
Quasi-periodic, short-period injections of relativistic electrons have been observed in both Jupiter’s and Saturn’s magnetospheres, but understanding their origin or significance has been challenging, primarily due to the limited number of in-situ observations of such events by past flyby missions. Here we present the first survey of such injections in an outer planetary magnetosphere using almost nine years of energetic charged particle and magnetic field measurements at Saturn. We focus on events with a characteristic period of about 60–70 min (QP60, where QP stands for quasi-periodic). We find that the majority of QP60, which are very common in the outer magnetosphere, map outside Titan’s orbit. QP60 are also observed over a very wide range of local times and latitudes. A local time asymmetry in their distribution is the most striking feature, with QP60 at dusk being between 5 and 25 times more frequent than at dawn. Field-line tracing and pitch angle distributions suggest that most events at dusk reside on closed field lines. They are distributed either near the magnetopause, or, in the case of the post-dusk (or pre-midnight) sector, up to about 30 RS inside it, along an area extending parallel to the dawn–dusk direction. QP60 at dawn map either on open field lines and/or near the magnetopause. Both the asymmetries and varying mapping characteristics as a function of local time indicate that generation of QP60 cannot be assigned to a single process. The locations of QP60 seem to trace sites that reconnection is expected to take place. In that respect, the subset of events observed post-dusk and deep inside the magnetopause may be directly or indirectly linked to the Vasyliunas reconnection cycle, while magnetopause reconnection/Kelvin–Helmholtz (KH) instability could be invoked to explain all other events at the duskside. Using similar arguments, injections at the dawnside magnetosphere may result from solar-wind induced storm